Երվանդունյաց Հայաստանի հողատիրության ձևերի հարցի շուրջ(մ.թ.ա. IV-III դդ.) - Պողոսյան, Արմեն (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
Because of the lack of primary sources concerning to the kingdom of Yervandids in the IV-III centuries BC, many questions still need to be studied. This article is an attempt to refer to the forms of land ownership existing in Armenia during the reign of the Yervandids, in connection with which the data of the original sources, particularly in the Greek inscriptions of Armavir and Aramaic inscriptions of king Artashes are examined, as well as evidencie of medieval Armenian historians. A comparison of the available data leads to the following conclusions: a) the land relations of the Yervandid era were characterized by certain administrative and economic features of the Achaemenid period, which existed in the satrapy of Armenia; on the other hand, in the land relations of the period of interest, there were such phenomena, which in contemporary armenology are considered as inherited from the earlier stage; b) in the IV and III centuries BC private property was not fully formed c) during the unstable reign of king Yervand some struggle between private and communal landowners began, which seems to have become even stronger during the reign of Artashes I, who followed Yervand.
Keywords: Պատմություն